Inventory and production management in supply chains /Edward R. Silver, University of Calgary (retired), Alberta, Canada, David F. Pyke, University of San Diego, California, USA, Douglas J. Thomas, Penn State University, Pennsylvania, USA - Silver, Edward A.(Edward Allen),1937-author
Revised edition of Inventory management and production planning and scheduling.